Through-the-scope Polyethylene Balloon Dilations in Benign Corrosive Esophageal Stricture Complicated with Temporomandibular Joint Dislocation - Elli Arsita; Achmad Fauzi; Jeffri Gunawan; Kaka Renaldi; Ari Fahrial Syam; Murdani Abdullah; Marcellus Simadibrata; Dadang Makmun; Chudahman Manan; Abdul Aziz Rani; Daldiyono Daldiyono (The Indonesian Society for Digestive Endoscopy, 2012)
Esophageal dilation is a non-surgical management for anatomic and functional abnormalities causing both benign and malignant esophageal stricture. The basic goals of stricture dilation include safe and efficacious lumenal enlargement plus prevention of restenosis. These could be achieved using through- the-scope (TTS) balloon dilations, ranged in diameter of 4 to 40 mm, they will allow dilation of previously inaccessible strictures in the esophagus, stomach, small bowel, and colon. There are 5,000–15,000 cases of stricture due to ingestion of corrosive substances in United States every year. The following case would demonstrate a 28-year-old male with depressive disorder who attempted a suicide by ingesting corrosive substances two months before admission. Subsequently he started having difficulty in swallowing even soft foods. The complaint was gradually increasing until a month before admission he went through endoscopic examination and a corrosive esophageal stricture found. Hence after, he underwent dilation using Savary bouginage with fluoroscopy and through-the-scope (TTS) balloon dilations. The patient underwent a series of dilation treatment and demonstrated vigorous improvement. Problems raised as the patient was complicated with temporomandibular joint (TMJ) dislocation due to traumatic injury after ingesting corrosive substances. The consideration in management of esophageal stricture with complications will be discussed further in this article. Keywords: esophageal stricture, corrosive substances, dysphagia, temporomandibular joint dislocation, through-the-scope polyethylene balloon dilation